2003
DOI: 10.1073/pnas.1733696100
|View full text |Cite
|
Sign up to set email alerts
|

On the interactions between atmospheric radicals and cloud droplets: A molecular picture of the interface

Abstract: How gas-phase materials become incorporated with cloud droplets has been an intriguing subject for decades, and considerable work has been done to understand the interactions between closed-shell molecules and liquid water. The interactions between open-shell radical species and liquid-phase cloud droplets, however, are not well understood. To probe these interactions we used quantum chemistry calculations to predict the energetics of the hydroperoxy radical (HO2) in the presence of an (H2O)20 spherical water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 16 publications
5
52
0
Order By: Relevance
“…In very recent studies of the Francisco group, [94,95] an (H 2 O) 20 spherical cage was used as a model of a cloud droplet. This model was chosen because it is the perfect balance between being large enough to contain an HOOC radical and small enough for quantum chemistry optimizations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In very recent studies of the Francisco group, [94,95] an (H 2 O) 20 spherical cage was used as a model of a cloud droplet. This model was chosen because it is the perfect balance between being large enough to contain an HOOC radical and small enough for quantum chemistry optimizations.…”
mentioning
confidence: 99%
“…Three stable conformations of (H 2 O) 20 ·HOOC were located. [94] The most stable one is a cyclic structure with a HOOC radical coordinated on two outermost water molecules of the (H 2 O) 20 cluster. In the most stable conformation, HOOC forms a seven-membered ring [···HÀOÀO···HÀO(H)···HÀOÀH···].…”
mentioning
confidence: 99%
“…First, we have considered the interaction between the hydroperoxyl radical and the (H 2 O) 20 water cluster in a similar way to that reported recently by Shi et al [40] We have found six different ways through which the HO 2 radical interacts with the edges of a water surface with similar stabilities, the most stable being C1 with a computed binding energy of 12.1 kcal mol…”
Section: Resultsmentioning
confidence: 82%
“…The interest in these complexes lies in the high stability of some hydrogen bonds formed by HO 2 (in particular, HO 2 has been shown to be a better proton donor than water). In addition, the interaction of HO 2 with a cluster of 20 water molecules has been studied by Shi et al, [40] who considered the radical both outside and inside the cluster. Moreover, Iyengar [41] has performed a dynamic study of the hydroperoxyl radical in water clusters of various sizes.…”
Section: Introductionmentioning
confidence: 99%
“…However, chaotropic ions with low surface charge density and/or high polarizability (such as Cl -, Br -, I -, HO 2 -and O 2 -) will favor the gas-liquid interfaces (Garrett, 2004;Jungwirth and Winter, 2008) as they only interact weakly with water but are influenced favorably by the highly polarized surface. Aqueous radicals also prefer to reside at such interfaces (Roeselová al, 2004), as do some molecular species that prefer to hydrogen bond on the outside of clathrate-like structures, like superoxide (Shi et al 2003). Small cations are found away from the interface towards the bulk where their requirement for efficient hydration may be satisfied.…”
Section: Surface Tension and Related Thermodynamicsmentioning
confidence: 99%